Haptic demonstrations of kitchen tasks - Jagadeesan, Kirish Deepan (Nanyang Technological University, 2022)
A sensorised kitchen knife is fabricated with the aims of haptic explorations and demonstrations. In this thesis, we cover the design of such a tool and the prototyp- ing considerations. The calibration of a 6-axis F/T sensor with the use of a 7-DOF robot arm is demonstrated. The experimental protocol for collecting data of forces and torques with pose data is evaluated. Simple experiments are conducted to analyse the efficacy of the tool and the embedded systems.